"As Soon as They Hear 'Undocumented, ' They Stop Advising": Theorizing a (Sub)conscious Evasion of Responsibility from Institutional Agents to Undocumented Students. Issue 3 (4th May 2021) - Castrellón, Liliana E.
Abstract: While nearly 100, 000 undocumented students in the United States graduate from high schools every year, a precarious national policy landscape exists that limits their higher education options. In addition to the structural and policy-level barriers to higher education for undocumented students, institutional agents might also enact barriers through individual practices. This qualitative study utilizes diffusion of responsibility and critical race theory to bring forward the experiences of undocumented students and institutional agents at Great Basin University (GBU). The findings presented here include, (sub)conscious evasion of responsibility and "all students" as white traditional students. (Sub)conscious evasion of responsibility refers to when institutional agents engage in a diffusion of responsibility and rely solely on diversity-affiliated offices to serve undocumented students. This study suggests that undocumented students are left out of the "all students" narrative and argues that higher education institutional agents cannot be ready to serve all students until they are undocuready . Implications point to the urgency of training institutional agents and shifting the culture of higher education institutions to center the needs of undocumented students.